Effect of crumb cellular structure characterized by image analysis on cake softness. Issue 3 (7th November 2017) - Dewaest, Marine; Villemejane, Cindy; Berland, Sophie; Neron, Stéphane; Clement, Jérôme; Verel, Aliette; Michon, Camille
Abstract: Sponge cake is a cereal product characterized by an aerated crumb and appreciated for its softness. When formulating such product, it is interesting to be able to characterize the crumb structure using image analysis and to bring knowledge about the effects of the crumb cellular structure on its mechanical properties which contribute to softness. An image analysis method based on mathematical morphology was adapted from the one developed for bread crumb. In order to evaluate its ability to discriminate cellular structures, series of cakes were prepared using two rather similar emulsifiers but also using flours with different aging times before use. The mechanical properties of the crumbs of these different cakes were also characterized. It allowed a cell structure classification taking into account cell size and homogeneity, but also cell wall thickness and the number of holes in the walls. Interestingly, the cellular structure differences had a larger impact on the aerated crumb Young modulus than the wall firmness. Increasing the aging time of flour before use leads to the production of firmer crumbs due to coarser and inhomogeneous cellular structures. Changing the composition of the emulsifier may change the cellular structure and, depending on the type of the structural changes, have an impact on the firmness of the crumb. Practical applications: Cellular structure rather than cell wall firmness was found to impact cake crumb firmness. The new fast and automated tool for cake crumb structure analysis allows detecting quickly any change in cell size or homogeneity but also cell wall thickness and number of holes in the walls (openness degree). To obtain a softer crumb, it seems that options are to decrease the cell size and the cell wall thickness and/or to increase the openness degree. It is then possible to easily evaluate the effects of ingredients (flour composition, emulsifier …) or change in the process on the crumb structure and thus its softness. Moreover, this image analysis is a very efficient tool for quality control.